Complications associated with the use of hyaluronic acid and their management - a literature review - Magdalena Turczynowicz; Karina Lewandowska; Wojciech Janikowski; Agnieszka Jóźwicka; Natalia Radwańska; Weronika Górska; Jerzy Król (Quality in Sport)
Introduction: Aesthetic medicine is a rapidly growing field, as evidenced by statistics from the American Society of Plastic Surgeons. Like any medical procedure, treatments with hyaluronic acid (HA) fillers carry a risk of complications or adverse effects. These complications can be broadly categorized into non-vascular and vascular events. Non-vascular complications include nodules, granulomas, oedema, Tyndall effect, infections, and biofilm formation. Vascular complications encompass ischemia, necrosis, and severe outcomes such as blindness or other visual impairments.